Redescription of Polynemula, with description of a new species of Polynema (Doriclytus) from Argentina (Hymenoptera: Mymaridae) - Triapitsyn, Serguei V.; Aquino, Daniel A. (Zootaxa, 2008)
The little known Neotropical genus Polynemula Ogloblin (Mymaridae) and its type species P. rufosignata Ogloblin are redescribed based on the type material and a recently collected female specimen from Buenos Aires Province, Argentina. A new species of Polynema Haliday from the newly defined pallidiventre species group of Polynema (Doriclytus Foerster), P. (D.) nupogodi sp. n., is described from Argentina and the only other species in this new group, P. (D.) pallidiventre (Ogloblin), is redescribed. A key to the two species of this group is provided.